Efficacy and safety of bevacizumab in combination with docetaxel for the first-line treatment of elderly patients with locally recurrent or metastatic breast cancer: results from AVADO - Pivot, Xavier; Schneeweiss, Andreas; Verma, Shailendra; Thomssen, Christoph; Passos-Coelho, José Luis; Benedetti, Giovanni; Ciruelos, Eva; von Moos, Roger; Chang, Hong-Tai; Duenne, Anja-Alexandra; Miles, David W. (European journal of cancer, 2011)
BACKGROUND: Oncologic treatment in elderly patients is challenging, due to comorbidities, often impaired organ function, limited clinical trial evidence, inadequate guidelines and no consistent 'elderly' definition. We report exploratory sub-analyses of safety and efficacy in elderly patients, defined as ⩾ 65years old, in AVastin And DOcetaxel (AVADO) receiving first-line bevacizumab plus docetaxel for metastatic breast cancer (mBC). - PATIENTS AND METHODS: Patients with HER2-negative, locally recurrent or mBC were randomised to 3-weekly docetaxel (100mg/m(2)) with placebo, bevacizumab 7.5mg/kg or bevacizumab 15 mg/kg, for 9 cycles or until disease progression or unacceptable toxicity. Patients had no prior chemotherapy for mBC. - RESULTS: Progression-free survival (PFS) was increased with bevacizumab in the elderly subpopulation (n=127), the effect being greater with higher dose (hazard ratio=0.63 [95% confidence interval (CI) 0.383-1.032] versus 0.76 [95% CI: 0.46-1.262], respectively). PFS was numerically similar in the elderly and overall populations, but the former failed to achieve statistical significance. Overall response rates for docetaxel plus placebo, bevacizumab 7.5mg/kg and 15 mg/kg were 44.7%, 36.6% and 50.0%, respectively. Effects on survival were not statistically significant. Bevacizumab was well tolerated in elderly patients, the most common adverse effects were neutropenia and febrile neutropenia; there was no excess of grade⩾3 cardiovascular events. There was no clear correlation between baseline hypertension and its development during study treatment. - CONCLUSIONS: In this exploratory sub-analysis in AVADO, bevacizumab plus docetaxel showed efficacy in elderly patients similar to the overall study population. There were no unexpected safety signals in patients aged 65 years or older.
Gesehen am 15.12.2022